Inovasi Transportasi Publik dan Kepuasan Masyarakat: Studi atas Layanan Bus Trans Banyumas - Sari, Yunita Ratna; Salsabih, Zibran Faical (Indonesian Democracy Research Center, 2024)
Public service is a fundamental responsibility of the government in meeting the needs of society while simultaneously improving the quality of life of its citizens. Public transportation serves as one of the crucial instruments of service delivery as it supports mobility, reduces congestion, and decreases the reliance on private vehicles. Banyumas Regency, as a center of administration, education, and commerce, faces increasingly complex transportation needs along with population growth and urbanization. To address this challenge, the local government in collaboration with the Ministry of Transportation launched the Trans Banyumas Bus Rapid Transit (BRT) service under the Buy The Service (BTS) program in December 2021. This study employs a descriptive qualitative method with a library research approach. Data were obtained from academic literature, official documents, and previous studies, and were analyzed to understand the role of Trans Banyumas as an innovation in public service delivery. The findings show that Trans Banyumas operates with 52 buses across three main corridors, with a fare of IDR 3,900 for the general public and IDR 2,000 for students. This service is considered capable of reducing dependence on private vehicles, minimizing pollution, and providing a more efficient mobility alternative. The Customer Satisfaction Index (CSI) of 82.31 percent indicates that users are generally satisfied with the service, although challenges remain regarding limited fleet availability, inconsistent scheduling, and insufficient access to bus stops. Beyond supporting daily mobility, Trans Banyumas also contributes to regional tourism and economic development by connecting tourist destinations, terminals, and train stations. Therefore, Trans Banyumas can be regarded as a public service innovation oriented toward sustainability.